Omnichannel Marketing on Integrated Retail Store in Indonesia - Stephanny Lianardo (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2022)
Omnichannel marketing should focus on creating an immersive environment in order to create a seamless experience for the customers. In this research, we are looking into the omnichannel marketing applied by PT. Erafone DotCom to integrate their fairly new online platform with their existing physical store and the public perspective toward it. We find out that despite the public being familiar with their physical store, the public is still largely unaware and unfamiliar with the existence of eraspace.com as the online platform of Erafone thus rendering the omnichannel marketing to be less effective. We also look into the public perspective of the idea of omnichannel marketing that has been applied by PT. Erafone DotCom and analyze how to improve the public awareness about eraspace.com and what strategy to improve the omnichannel marketing that has been applied in order to create an immersive environment for the customers to have seamless experience in shopping with Erafone and/or eraspace.com.